2015
DOI: 10.1371/journal.pone.0131165
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Active Components of Yokukansan, a Traditional Japanese Herbal Medicine after a Single Oral Administration to Healthy Japanese Volunteers: A Cross-Over, Randomized Study

Abstract: ContextYokukansan (YKS) is a traditional Japanese herbal medicine called kampo medicine in Japan. Its extract comprises seven crude drugs: Atractylodis lanceae rhizoma, Poria, Cnidii rhizoma, Uncariae uncis cum ramulus, Angelicae radix, Bupleuri radix, and Glycyrrhizae radix. YKS is used to treat neurosis, insomnia, as well as behavioral and psychological symptoms of dementia.ObjectiveTo confirm the exposure and pharmacokinetics of the active components of YKS in healthy volunteers.Design, Setting, and Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
(30 reference statements)
2
19
0
Order By: Relevance
“…In this study, we used the somatosensory system of mice to examine the possible adverse effects of yokukansan. The pharmacokinetics of the active components of yokukansan, such as geissoschizine methyl ether (GM), hirsuteine and 18β‐glycyrrhetinic acid (GA) have been investigated in healthy Japanese volunteers . It was found that the plasma GA concentration was high compared with that of GM and of hirsuteine because GM and hirsuteine are rapidly eliminated, with half‐lives of approximately 2 h, whereas the half‐life of GA was approximately 10 h .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used the somatosensory system of mice to examine the possible adverse effects of yokukansan. The pharmacokinetics of the active components of yokukansan, such as geissoschizine methyl ether (GM), hirsuteine and 18β‐glycyrrhetinic acid (GA) have been investigated in healthy Japanese volunteers . It was found that the plasma GA concentration was high compared with that of GM and of hirsuteine because GM and hirsuteine are rapidly eliminated, with half‐lives of approximately 2 h, whereas the half‐life of GA was approximately 10 h .…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of the active components of yokukansan, such as geissoschizine methyl ether (GM), hirsuteine and 18β‐glycyrrhetinic acid (GA) have been investigated in healthy Japanese volunteers . It was found that the plasma GA concentration was high compared with that of GM and of hirsuteine because GM and hirsuteine are rapidly eliminated, with half‐lives of approximately 2 h, whereas the half‐life of GA was approximately 10 h . Interestingly, the plasma GM and hirsuteine concentrations were almost identical between mice and humans .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, yokukansan has the potential to increase hippocampal neurogenesis associated with the suppression of activated microglia 22 . Furthermore, several studies related to pharmacokinetics of yokukansan have demonstrated that several compounds contained to yokukansan migrate to both plasma and brain after oral administration in in vivo experiments 23, 24. According to these studies, it is reasonable to consider that yokukansan and its compounds would distribute to the brain by oral administration and be effective for the treatment of depression or anxiety disorder and the mechanism may be similar to those of antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…We were therefore unable to compare the dose of the ingredients in YKS used in the present study with that in the previous in vitro studies. In one clinical study, the pharmacokinetic parameters of several active ingredients of YKS, such as 18β-glycyrrhetinic acid and geissoschizine methyl ether, were determined in healthy subjects, 36) but there are presently no data available regarding the blood concentrations of the ingredients listed in Supplementary Table 1. In addition, we were unable to collect enough blood samples to assess the concentration of each ingredient of these herbal components.…”
Section: Discussionmentioning
confidence: 99%